THE CRITICAL ROLE OF SYSTEMS DESIGN IN CLOUD-BASED MACHINE LEARNING PLATFORMS - Snehansh Devera Konda (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This in-depth article explores how the architecture and efficacy of cloud-based machine learning platforms are influenced by basic systems design principles. It illustrates how fundamental software engineering ideas, such as modularity, separation of concerns, and design patterns, serve as the cornerstone of reliable machine learning systems by using an examination of 500 enterprise implementations. With case studies demonstrating how appropriate service boundaries reduce inter-system dependencies by 72% and how event-driven architectures enable ML model scaling across 850,000 daily predictions per tenant, the article investigates how architectural choices in distributed systems design directly impact ML platform capabilities. With appropriately implemented CQRS patterns lowering response times by 65%, the article shows how system design decisions in data flow patterns affect model serving latency. By analyzing fault tolerance methods, it shows that bulkhead isolation and circuit breaker layouts can reduce cascading failures in machine learning pipelines by 76%. The article also examines how systems design principles inform the creation of API contracts, finding that interface segregation and versioning techniques cut down on breaking changes during ML model updates by 82%. It offers a paradigm for architects to make well-informed decisions on system boundaries, component interactions, and architectural patterns unique to ML workloads by concentrating on the nexus between systems design and ML platforms. The results highlight how ML platforms may facilitate quick iteration in ML development cycles and meet enterprise needs for scalability, maintainability, and reliability through appropriate systems architecture.